Social Sciences as Sorcery (excerpt) - Andreski, Stanislav (Journal of Economic Sociology, 2025)
In quantitative terms, the social sciences are experiencing unprecedented growth today. However, contrary to the enthusiasm expressed by most specialists, Professor Andreski draws attention to the fact that the flow of publications in the social sciences actually reveals a deficit of new ideas. The current agenda is dominated by vague verbosity, endless repetitions of banalities, and disguised propaganda. According to the British sociologist, the average quality of publications has declined. The book Social Sciences as Sorcery is largely aimed not only at providing evidence to support the author’s diagnosis of the social sciences but also at finding explanations and solutions for the current state of affairs. Professor Andreski argues that this shift toward the sterility of research on human life arises from the dominant cultural, political, and economic trends of our time. Nevertheless, he describes his view of the prospects for the social sciences as one of “desperate optimism”—“desperate” because he does not see how our civilization could survive without significant progress in understanding humanity and society. The journal “Economic Sociology” publishes the second chapter of the book “The Sorcerer’s Dilemma”, in which the author examines some of the key intellectual difficulties in the study of society and culture.